Assessment of pedestrian facilities along Marcos Highway - Marcelo, Kelvin Ryan S.; Salvador, Juan Pablo B.
Pedestrian fac ilities in the country have been in various conditions due to several factors. The traffic condition affects the pedestrian facility since vehicles affect the pedestrians' travel. It also depends on how much priority was given by the local authorities in developing these facilities. This study aims to know what can be considered as the standards for a safe and efficient pedestrian facility that can be used in the Philippine setting. The area of the study is the pedestrian facilities along Marcos Highway. The study involves assessing the condition of the pedestrian facilities along the highway and come up with an overall rating using the Global Walkability Index rating method. Walkability can be associated in terms of safety security, and convenience of pedestrians. The rating is a product of the parameter score, length of surveyed stretch and pedestrian count. Further analysis of the results shows the need to apply correction in order to get the right rating. It was then concluded that Marcos Highway is walkable overall. Evaluating the walkability ratings per road stretch shows the need for improvement shown by the Global Walkability Index parameters. Improvements such as widening of the walking path and installation of lights and footbridges are among the recommended by the researchers. For future studies, the researchers also recommend some modifications on the original methodology. This is to use a more effective assessment or pedestrian facilities in the country.